To what extent does the English Premier League address CSR? - Varsani, Rajesh (2009)
Various research has looked into the expansion of CSR within the management field. However CSR can vary substantially between different industries such as its application in sport. There is a growing interest in this field as stakeholders have placed greater emphasis on professional sports teams to have a social responsibility. This expectation has been largely fuelled by the Olympics movement – the single largest sporting event across the world - who have asked potential host cities to draw up plans on how they will host the event with ‘sustainability’ in mind. The forthcoming London 2012 Olympics boasts ‘sustainability’ at the heart of their plans covering areas such as healthy living, climate change, waste and providing facilities for the local community for many years to come. This expectation has transferred into other sporting events such as the National Football League in America (Babiak K and Wolfe R, 2006) and more recently in football across Europe especially the English Premier League as a result of commercialization which has seen the league declared the richest in the world (Dobson, S and Goddard J, 2001).